Forensic science and the right to access to justice: Testing the efficacy of self-examination intimate DNA swabs to enhance victim-centred responses to sexual violence in low-resource environments. Issue 5 (September 2017) - Smith, Lisa L.; Wetton, Jon H.; Lall, Gurdeep K.M.; Flowe, Heather D.; Jobling, Mark A.
Abstract: In developed countries, DNA profiling routinely forms part of the forensic strategy in the investigation of sexual violence. Medical examinations provide opportunities for recovering DNA evidence from intimate swabs, which can be particularly probative in cases where the identity of the perpetrator is unknown and proof of intercourse between two people is required. In low-resource environments, such as developing countries, remote geographic locations, conflict (and post-conflict) affected regions and displaced communities where access to medical examinations is lacking, DNA evidence is not available to support prosecutions and perpetrators are rarely identified and held accountable for crimes of sexual violence. This paper reports the results of a proof-of-concept study testing the efficacy of a novel self-examination intimate swab designed for recovering DNA following unprotected sexual intercourse. The results of this study corroborate previous research which has demonstrated that male DNA profiles can be successfully recovered by post-coital, self-examination methods, and discusses how this novel approach could enable the integration of DNA evidence into victim-centred approaches to investigating and prosecuting sexual violence in low-resource environments. The results and discussion challenge the prevailing assumption that intimate DNA swabs must be collected by trained medical professionals in order to be of evidential value. Highlights: There are barriers to DNA evidence in cases of sexual violence in low-resource environments. A novel self-examination intimate swab is proposed and tested. This novel swab overcomes barriers to accessing medical services. This method can enhance access to justice to victims.